TANGGUNG JAWAB DIREKSI DALAM KEPAILITAN PERSEROAN TERBATAS DITINJAU DARI ASPEK PIDANA - , Anas Malik, SH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the responsibility of directors in bankruptcy in the review of the criminal aspect as well as other provisions governing the criminal sanctions against those associated with the bankruptcy of the limited company. This research is normative, because in this study used secondary data, in which secondary data is obtained by doing library research. Materials research is to collect research materials in libraries as a basic foundation and the main assessment tool in research. Data collection techniques used in research techniques that refer to materials which are documented by means of studies that documentation was done by studying, studying and reviewing the materials in the form of secondary data, either in the form of books as well as legislation relating to research materials . Data analysis focused on a deductive method as the main grip, and the inductive method as a good supporting work, a portrait that is expected to be clear about the responsibility of directors in a limited liability company bankruptcy is viewed from the criminal aspect. The result showed that members of the board of the directors which has resulted in a loss to the debtor company also sentenced under Article 398 the Criminal Penal Code and Article 403 the Criminal Penal Code, which threaten criminal penalties for the management of the debtor in the from of legal entities that assist or permit actions as referrd to in Aticle 398 was. Other provisions that govern the criminal sanctions against those associated with bankruptcy, the limited company also arranged in the draft Penal Code.